Successful treatment of recalcitrant plantar warts with pulsed dye laser - Vukovska, Rebeka (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Plantar warts caused by human papillomavirus (HPV) are often resistant to standard treatments, significantly affecting patients’ quality of life. Pulsed dye laser (PDL) therapy has emerged as a promising alternative for refractory cases. Methods: Four patients (three males, one female; ages 15 to 45) with recalcitrant plantar warts unresponsive to cryotherapy, curettage, and topical agents were treated with PDL. Each underwent three sessions spaced 3 weeks apart, using a fluence of 13.50 J/ cm2 and a pulse duration of 1.5 ms. Outcomes assessed included lesion resolution, recurrence rates, and adverse effects. Results: All patients achieved complete wart resolution after three PDL sessions. By the second session, vascular coagulation was evident, leading to significant lesion reduction. No adverse effects such as scarring or pigmentation changes were reported, and no recurrences were observed during a 3-month follow-up. Conclusions: Among laser therapies, PDL demonstrates excellent outcomes with minimal adverse effects in treating refractory plantar warts. Further studies are warranted to validate these findings in larger populations.
Keywords: human papillomavirus; humani papiloma virus; plantar warts; plantarne bradavice; pulsed dye laser; pulzni barvni laser; refractory warts; refraktorne bradavice; treatment; zdravljenje